WORKSHOP PENYUSUNAN SKRIPSI, PUBLIKASI ILMIAH DAN PEMBUATAN POSTER ILMIAH BAGI MAHASISWA TINGKAT AKHIR JAKARTA GLOBAL UNIVERSITY - Mohamad Zaenudin; Dian Nugraha; Safira Faizah (Universitas Mataram, 2023)
Enhancing the academic capabilities of senior-level students in higher education involves a series of pivotal tasks such as completing a thesis, publishing scholarly works, and creating scientific posters. However, the execution of these tasks still encounters several challenges, including limitations in academic writing skills, a restricted understanding of enhancing writing quality, as well as a deficiency in comprehending ethical writing aspects, such as avoiding plagiarism and employing proper citation methods. Moreover, there are challenges in embarking on the path toward publication and within the overall writing process. In this context, the purpose of organizing the workshop is to provide an in-depth understanding of essential elements within these three areas. This encompasses enhancing writing skills, enriching the understanding of ethical writing to mitigate instances of plagiarism, and ensuring accurate citation practices. Furthermore, it aids participants in grasping research requisites and guidelines, while elevating awareness of academic norms. Crafting a thesis necessitates an understanding of fundamental principles and established regulations, while scholarly writing involves formulating strategies and meticulously presenting research outcomes. The creation of scientific posters also plays a crucial role in effectively conveying research findings visually. This workshop offers practical guidance and training in these aspects, including elucidating formats, arranging layouts, and employing tools such as the Canva application. The outcomes of this workshop materialize in the form of attraction, enthusiasm, and a profound understanding among participants regarding thesis writing methods, scholarly work composition, and research poster presentations. Participants have mastered the use of the citation tool Mendeley, as well as the implementation of Canva in designing research posters. This workshop has been successfully conducted and serves as a platform to advance the academic careers of participants. The workshop is deemed successful to sharpen the skills and self-confidence of participants in thesis writing, precise citation utilization, and crafting scholarly writing effectively.